Comparison of Risk Factors, Severity and Outcome between Lacunar and Non-Lacunar Stroke in a Tertiary Care Center in Sri Lanka: A Descriptive Study - Perera, N.D.; Bandara, K.M.; Ranasinghe, I.R.; Gunathilake, S.B. (Sri Lanka Medical Association, 2015)
This study compares demography, risk factors and outcome of lacunar (LAC) and non-lacunar (non-LAC) strokes from the prospective hospital based stroke registry at Colombo South Teaching Hospital from 1st March 2012 to 30th June 2013. Data on admission, discharge and at 28 days after discharge were analysed. There were 229 ischaemic stroke (IS) patients. Average age was 65.7 years (SD 12.2, range 34-94) and 116 (50.7%) were males. LAC (n=130, 56.8%) were common than non-LAC (n=99, 43.2%). There were 75 (64.7%) males and 55 (48.7%) fem ales in the LAC group (adjusted OR 2.1, 95% CI 1.08-4.29). Atrial fibrillation was less frequent among LAC stroke (OR 0.3, 95% CI 0.09 -0.99). Hypertension, diabetes, smoking, dyslipidaemia did not differ in the two groups. Lower NIHSS (5.34 Vs 6.6, p= 0.053), higher GCS (14.7 Vs 13.3, p=0.001) were seen in LAC. Disability (MRS, Barthel index) on discharge, at 28 days and mortality during hospital stay and within 28 days was lower in the LAC group (p <0.001).
Keywords: lacunar stroke; non-lacunar stroke; demography; risk factors